PENGARUH STRES KERJA DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN - Inna Nisawati Mardiani; Nur Khamdanah (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
Performance is a real behavior that is displayed by everyone as work performance is produced by employees by following the work environment in the company. Employee performance is a very important thing in the company's efforts to achieve goals. The purpose of this study was to determine the effect of work stress and workload on employee performance. This type of research is quantitative. This research design is included in causal associative research. The population in this study were all employees totaling 129 employees. The sampling method used in this research is purposive sampling. The sample in this study was 100 employees of the production department. The data collection technique used in this study was a questionnaire. The validity test will be carried out using the product moment correlation formula and the reliability test using the Cronbach alpha formula. To prove the research hypothesis, a statistical test is carried out in the form of multiple linear regression analysis. The data analysis technique used multiple linear regression analysis. The results showed that work stress and workload affected employee performance.